2011
DOI: 10.1186/1745-6150-6-40
|View full text |Cite
|
Sign up to set email alerts
|

Shift in the isoelectric-point of milk proteins as a consequence of adaptive divergence between the milks of mammalian species

Abstract: BackgroundMilk proteins are required to proceed through a variety of conditions of radically varying pH, which are not identical across mammalian digestive systems. We wished to investigate if the shifts in these requirements have resulted in marked changes in the isoelectric point and charge of milk proteins during evolution.ResultsWe investigated nine major milk proteins in 13 mammals. In comparison with a group of orthologous non-milk proteins, we found that 3 proteins κ-casein, lactadherin, and muc1 have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…The theoretical pI (isoelectric point) of a protein is important for solubility, subcellular localization and interaction [32,33]. Thus, the shift of the value is always considered as the changes of the protein functions [34]. We found that silkworm orphan proteins have significantly higher average pI value (9.18 ± 2.41) than nonorphan proteins (7.62 ± 2.09) (Mann-Whitney U test, P < 0.001) ( Fig.…”
Section: Features Of the Silkworm Ogsmentioning
confidence: 75%
“…The theoretical pI (isoelectric point) of a protein is important for solubility, subcellular localization and interaction [32,33]. Thus, the shift of the value is always considered as the changes of the protein functions [34]. We found that silkworm orphan proteins have significantly higher average pI value (9.18 ± 2.41) than nonorphan proteins (7.62 ± 2.09) (Mann-Whitney U test, P < 0.001) ( Fig.…”
Section: Features Of the Silkworm Ogsmentioning
confidence: 75%
“…The first amino acid change has no effect on the polarity of the mature protein, whereas the second slightly shifts the predicted isoelectric point (pI) from 4.78 to 4.85 as consequence of the different chemical properties of the involved amino acid, from neutral (tyrosine) to basic (histidine). As pI and charge of milk proteins are important for their interactions and properties (Khaldi and Shield, 2011), protein variants were submitted to the NetSurfP ver. 1.1 software (http://www.cbs.dtu.dk/ services/NetSurfP/) to predict the secondary structure and detect potential modifications of the surface accessibility for the investigated amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…The biochemical differences, nature and location of amino acid substitution can affect the protein in various ways and is therefore important to determine whether it can alter the protein function. Isoelectric focusing point (pI) and charge is important for the solubility and interaction of a protein (Nandi et al, 2005;Khaldi and Shields, 2011). It is clear from the research that, pI of a protein can vary due to insertions, deletions, substitutions and the ecology of the organism (Kiraga et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Isoelectric focusing point (pI) and charge is important for the solubility and interaction of a protein (Nandi et al, 2005;Khaldi and Shields, 2011). Theoretical pI of the p53 proteins were predicted by using Bioinformatics tools and were observed 6.34 and 6.47 for the native and polymorphic respectively.…”
Section: 3973 Rs1042522 Polymorphism and Its Huge Review In Pakistanmentioning
confidence: 99%